Pengaruh Brand Image dan Kualitas Produk terhadap Keputusan Pembelian Smartphone Xiaomi - Jajang Suherman; Ricky Rohmanto Rohmanto; Abi Rachmadia Azhar Azhar (Ma'soem University, 2026)
Competition in the smartphone industry is increasingly intense, especially in the entry-level segment targeting lower to middle-class consumers. Xiaomi has become one of the favored brands because it can offer high specifications at affordable prices. This raises the question of how much product quality and price perception influence purchasing decisions, particularly in Bandung City. This study aims to analyze the influence of brand image and product quality on Xiaomi smartphone purchasing decisions, both partially and simultaneously. Using a quantitative approach, data were collected through questionnaires from 100 Xiaomi phone users in Bandung City selected through purposive sampling. This study is expected to provide input for business actors and marketers in designing effective strategies. The data processing was carried out using SPSS version 27 software with methods including validity test, reliability test, normality test, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that product quality and price perception have a significant effect on purchasing decisions, both individually and simultaneously. The coefficient of determination value reaches 62.5%, which means that these two variables explain most of the variation in consumer purchasing decisions. The conclusion of this study is that Brand Image has a significant effect on purchase decisions. The t-test results show that product quality has a significance value of 0.000 (p < 0.05) and a regression coefficient of 0.497. Product quality has a positive effect on purchase decisions, showing a significance value of 0.000 (p < 0.05) and a regression coefficient of 0.574. Brand image and product quality simultaneously have a significant effect on purchase decisions. The F-test results show a significance value of 0.000 (p < 0.05), indicating that both variables together have an effect on purchasing decisions. The coefficient of determination (R Square) value of 0.625 shows that 62.5% of the variation in purchasing decisions can be explained by product quality and price perception. The remaining 37.5% is explained by other variables not examined in this study.